Reactivity and mechanism of α-nucleophile scaffolds as catalytic organophosphate scavengers - Wong, Pamela T; Bhattacharjee, Somnath; Cannon, Jayme; Tang, Shengzhuang; Yang, Kelly; Bowden, Sierra; Varnau, Victoria; O'Konek, Jessica J; Choi, Seok Ki (Organic & biomolecular chemistry, 2019)
Despite their unique benefits imparted by their structure and reactivity, certain α-nucleophile molecules remain underexplored as chemical inactivators for the topical decontamination of reactive organophosphates (OPs). Here, we present a library of thirty α-nucleophile scaffolds, each designed with either a pyridinium aldoxime (PAM) or hydroxamic acid (HA) α-nucleophile core tethered to a polar or charged scaffold for optimized physicochemical properties and reactivity. These library compounds were screened for their abilities to catalyze the hydrolysis of a model OP, paraoxon (POX), in kinetic assays. These screening experiments led to the identification of multiple lead compounds with the ability to inactivate POX two- to four-times more rapidly than Dekon 139-the active ingredient currently used for skin decontamination of OPs. Our mechanistic studies, performed under variable pH and temperature conditions suggested that the differences in the reactivity and activation energy of these compounds are fundamentally attributable to the core nucleophilicity and p K a . Following their screening and mechanistic studies, select lead compounds were further evaluated and demonstrated greater efficacy than Dekon 139 in the topical decontamination of POX in an ex vivo porcine skin model. In addition to OP reactivity, several compounds in the PAM class displayed a dual mode of activity, as they retained the ability to reactivate POX-inhibited acetylcholine esterase (AChE). In summary, this report describes a rationale for the hydrophilic scaffold design of α-nucleophiles, and it offers advanced insights into their chemical reactivity, mechanism, and practical utility as OP decontaminants. Design and in vitro validation of polar α-nucleophile scaffolds that offer potent catalytic reactivity and practical utility for organophosphate decontamination.